2002
DOI: 10.1152/ajpheart.01029.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection mediated by sphingosine-1-phosphate and ganglioside GM-1 in wild-type and PKCε knockout mouse hearts

Abstract: Cardioprotection mediated by sphingosine-1-phosphate and ganglioside GM-1 in wild-type and PKC⑀ knockout mouse hearts. Am J Physiol Heart Circ Physiol 282: H1970-H1977, 2002. First published February 14, 2002 10.1152/ajpheart.01029.2001.-Sphingosine-1-phosphate (S1P) protects neonatal rat cardiac myocytes from hypoxic damage through unknown signaling pathways. We tested the hypothesis that S1P-induced cardioprotection requires activation by the ⑀-isoform of protein kinase C (PKC⑀) by subjecting hearts isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
132
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(141 citation statements)
references
References 29 publications
(49 reference statements)
8
132
1
Order By: Relevance
“…Maulik et al [23] initially showed that GM-1 can reduce I/R injury in an isolated rat heart by Langendorff technique and had suggested that the likely mechanisms included inhibition of calcium overloading and scavenging of free radicals generated during the reperfusion of myocardium. Recent studies by Jin et al [24] have confirmed that GM-1, which enhances endogenous sphingosine-1-phosphate production, reduces cardiac injury through PKCε-dependent intracellular pathways in an isolated mouse heart Langendorff model of ischemia-reperfusion injury.…”
Section: Sphingolipids and Myocardial I/r Injurymentioning
confidence: 92%
See 1 more Smart Citation
“…Maulik et al [23] initially showed that GM-1 can reduce I/R injury in an isolated rat heart by Langendorff technique and had suggested that the likely mechanisms included inhibition of calcium overloading and scavenging of free radicals generated during the reperfusion of myocardium. Recent studies by Jin et al [24] have confirmed that GM-1, which enhances endogenous sphingosine-1-phosphate production, reduces cardiac injury through PKCε-dependent intracellular pathways in an isolated mouse heart Langendorff model of ischemia-reperfusion injury.…”
Section: Sphingolipids and Myocardial I/r Injurymentioning
confidence: 92%
“…Unlike ceramide and sphingosine, S1P promotes cell growth, viability, mitosis and angiogenesis either through S1P receptors or intracellularly as a secondary messenger [34]. Jin et al [24] have shown that the cardioprotection conferred by the monoganglioside GM-1, which stimulates SK, is cardioprotective in part through increased generation of S1P. They have also shown that the cardioprotection conferred by myocardial ischemic preconditioning may also be mediated through PKCε mediated increase in SK activity [40].…”
Section: Sphingolipids and Myocardial I/r Injurymentioning
confidence: 99%
“…Creatine kinase (CK) activity in coronary effluent collected during reperfusion was measured using a commercial kit (Sigma) and corrected for flow rate and wet heart weight. After reperfusion, hearts were perfused with 1% triphenyltetrazolium chloride solution, fixed in 10% neutral buffered formalin, and sectioned (20). Planimetry of viable (stained) and necrotic (unstained) tissue was performed using NIH Image software.…”
Section: Methodsmentioning
confidence: 99%
“…1B). Cardioprotection in association with PKC activation has also been observed after stimulation with pharmacological agents such as adenosine A 1 receptor agonists (15), ␦ 1 -opioid receptor agonists (12,26), ethanol (19,27), sphingosine-1-phosphate (20), and ␣ 1 -adrenergic receptor agonists (9,28). Here we pretreated with PHE at concentrations selective for ␣ 1 -adrenergic receptor stimulation and improved LVDP recovery during reperfusion in wild-type but not PKC⑀ KO hearts (Fig.…”
Section: Normal Base-line Morphology and In Vivo Cardiac Function In mentioning
confidence: 99%
“…S1P has been shown to activate Akt (14,37,39), which has been associated with cell survival in cardiomyocytes (10,31,38). In addition, S1P has been shown to protect neonatal rat cardiomyocytes and perfused rabbit and mouse hearts from ischemic damage (5,18,19,22). However, neither the receptor subtype nor the signal-transduction pathways mediating these effects has been established, nor has an in vivo protective role for endogenously released S1P been demonstrated.…”
Section: ϫ/ϫmentioning
confidence: 99%